2019
DOI: 10.3389/fmicb.2019.02034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a pH-Tolerant Strain Cobetia sp. SASS1 and Its Phenol Degradation Performance Under Salinity Condition

Abstract: Biological treatment of complex saline phenolic wastewater remains a great challenge due to the low activity of bacterial populations under stressful conditions. Acid mine drainage (AMD) as a typically extreme environment, shaped unique AMD microbial communities. Microorganisms survived in the AMD environment have evolved various mechanisms of resistance to low pH, high salinity and toxic heavy metals. The primary goal of this work was to determine whether a strain isolated from an AMD could degrade phenol und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…SASS1 strain cells growth and phenol degradation were investigated at the optimal pH and salinity. Comparing with the control group, the OD600 value decreased remarkably but phenol degradation efficiencies increased from 4.7 to 10.2% while biodegradation time was lengthened from 10 to 40 h [30]. Other researchers revealed a strong inhibition effect of nickel during phenol biodegradation by Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…SASS1 strain cells growth and phenol degradation were investigated at the optimal pH and salinity. Comparing with the control group, the OD600 value decreased remarkably but phenol degradation efficiencies increased from 4.7 to 10.2% while biodegradation time was lengthened from 10 to 40 h [30]. Other researchers revealed a strong inhibition effect of nickel during phenol biodegradation by Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 84%
“…Phenol is a compound that inhibits the growth of the bacterial population. Due to mathematical simplicity Andrews model is extensive use for describing the growth on inhibitory substrates such as phenol [16,27,30]. The inhibitory growth kinetic equation is as follows:…”
Section: Modelling Kinetics Of Cell Growth On Phenolmentioning
confidence: 99%
“…SASS1, Candida tropicalis SDP-1, and Debaryomyces sp. JS4 (Jiang et al 2016;Mei et al 2019;Duraisamy et al 2020;Gong et al 2021). Under the conditions of heavy metal stress, Bacillus can produce a large number of extracellular secretions, such as organic acids, proteins, peptides, lipids, etc.…”
Section: The Influences On Phenol Biodegradationmentioning
confidence: 99%
“…In addition to phenol, industrial effluents also contain some heavy metals as co-pollutants with different composition and concentration, which are not only highly toxic, persistent and non-degradable, but also severely inhibit the degradation of phenol by microorganisms (Duraisamy et al 2020). At present, only a small number of studies have reported the microbial degradation efficiency of phenol under the condition of different heavy metals or toxic pollutions (Mei et al 2019;Xu et al 2021). Thus, the development of microorganisms with the ability to degrade phenol with high concentration and efficiency that can tolerate multiple organic pollutions, heavy metals and wide pH range, become promising candidates for the bioremediation of phenol wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…cqz5-12 [ 10 ]. At the same time, more and more information appears about Cobetia isolates, which are promising sources of unique enzymes and secondary metabolites degrading oil [ 11 ], bacterial biofilms [ 12 ], alginate [ 10 , 13 ], and phenol [ 14 ]. However, their species identification are complicated due to the high level of identity for their 16S rRNA genes and the absence of whole genome sequences for the type strains of known species, excluding from C. marina JCM 21022 T [ 8 ].…”
Section: Introductionmentioning
confidence: 99%